Strategi Pengembangan Objek Wisata Raewaya Hills di Desa Airmadidi Minahasa Utara - Adrah, Merry H.; Mekel, Rahel (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2024)
The purpose of this research is to develop a strategy for developing Raewaya Hills tourism objects in realizing sustainable tourism. In this study using qualitative research methods. The data sources used in this study were primary data obtained through direct observation at the location including land use patterns, physical condition of the land, accommodation, condition of facilities and infrastructure as well as secondary data in the form of notes from interviews with tourists, the community and the government. Based on the results of the research, it was concluded that the Raewaya Hills nature tourism area needs to be carried out with a strategy of redeveloping and repairing damaged facilities and adding facilities, this is done so that it can support tourism progress and can add to the attractiveness of Raewaya Hills natural tourism.